Bond Behavior of Steel-Recycled Aggregate Concrete Interface After High Temperatures and Spraying Water Cooling - Zhou, Chunheng; Cao, Jiazhang; Chen, Zongping (Frontiers in Materials, 2021)
Using recycled aggregate concrete (RAC) in steel reinforced concrete structure is an effective way to eliminate the adverse effects of recycled aggregate which has an excellent application prospect. Fire has a great destructiveness to steel reinforced recycled aggregate concrete (SRRAC) structure, hence the bond performance of SRRAC after high temperature, as the prerequisite for the composite between steel and RAC, is the key problem for structural safety and the corresponding safety assessment after fire. In this paper, the residual bond behaviors of steel-recycled aggregate concrete interface after different high temperatures and spraying water cooling were studied through the push-out test. The failure modes and load-slip curves were examined. The ultimate bond strength, residual bond strength and elastic bond shear stiffness of specimens after high temperature and cooling for the regime of spraying water were evaluated and compared to that of natural air. A parametric analysis of temperature, replacement percentage and studs was conducted. A calculation approach for the ultimate bond strength and residual bond strength of SRRAC after high temperature was developed base on the sensitive analysis of grey system theory and regression analysis. Results showed that the bond properties of SRRAC specimens after high temperature was decreased as exposure temperature increased. The cooling regime of spraying water has a more significant influence on the ultimate strength and residual strength than that of natural air. The specimens with studs on both flange and web have the highest bond properties after high temperature. In all the factors, the number of studs showed the largest grey relational degree to the bond strength of SRRAC. The developed approach provided a reliable prediction of bond strength for SRRAC after high temperature.